Características, funções e preservação digital do archivematica à luz da resolução nº 43 do conselho nacional de arquivos - Gomes, Wellington da Silva (2019)
The emergence of Information and Communication Technology (TIC) has given rise to a new paradigm in post-industrial society: that of technological evolution over information. This has led to the dynamization of the media used by computers and the Internet, especially in the diffusion of what is known as cyberspace. These changes also had an impact in the scientific fields that have as praxis the relation between the analysis and object: the information, adapting to the transformations caused by the technological progress, producing instruments to rationalize and control the increase of its registers. Thus, the transition from analog to digital documents proves unquestionably that TICs have enabled different forms of interaction between individuals, has altered the way of thinking information management in the virtual environment, mainly through the intermediation of hardware and software. In this way, free software plays an essential role in the storage and preservation of information, emphasizing Archivematica. In order to penetrate the aspects of functionalities and characteristics of said system that have eight guides responsible for the information packet process (SIP, AIP, DIP), it was taken as a point of analysis to Resolution nº 43 of CONARQ, which establishes guidelines for implementation of the so-called Trusted Archival Digital Repository (RDC-Arq). Thus, this research had the objective of evaluating Archivematica from the elements of Resolution nº 43. As a method, it presented a descriptive, documentary and qualitative character in comparative bias, confronting the tasks of the software in evaluation to the reliability requirements posted of the mentioned regulation. The results demonstrate the full compliance with the requirements of Resolution 43, which supports Archivematica as a Trusted Archival Digital Repository. It is concluded, then, that all the elements inserted in the mentioned directive were encompassed to such software, characterizing it as an RDC-Arq.